2003
DOI: 10.1074/jbc.m307832200
|View full text |Cite
|
Sign up to set email alerts
|

The Coactivator p/CIP/SRC-3 Facilitates Retinoic Acid Receptor Signaling via Recruitment of GCN5

Abstract: p/CIP/SRC-3 is a member of a family of steroid receptor coactivators/nuclear receptor coactivators (SRC/ NCoA) proteins that mediate the transcriptional effects of nuclear hormone receptors (NRs). Using deletion analysis we have mapped the location of two distinct activation domains in p/CIP (AD1 and AD2) capable of activating transcription in mammalian cells when fused to the Gal4-DNA binding domain. In addition to AD1 being coincident with the interaction domain for CBP, we demonstrate a novel in vivo intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 79 publications
1
27
0
Order By: Relevance
“…2A). This suggests that SUG-1 would contribute to RAR␣-dependent transcriptional activation as efficiency as SRC-3 (20,27). In contrast, knockdown of the other p160 coactivators, SRC-2 and SRC-1, had no effect (Fig.…”
Section: Sug-1 and Src-3 Contribute To The Transcription Of Ra Targetmentioning
confidence: 72%
“…2A). This suggests that SUG-1 would contribute to RAR␣-dependent transcriptional activation as efficiency as SRC-3 (20,27). In contrast, knockdown of the other p160 coactivators, SRC-2 and SRC-1, had no effect (Fig.…”
Section: Sug-1 and Src-3 Contribute To The Transcription Of Ra Targetmentioning
confidence: 72%
“…Yeast assays can be designed also to study mechanisms of coactivator function. For example, phenotypes conferred upon expression of hSRC-3 (Brown et al, 2003), GRIP1 and SRC-1 (Anafi et al, 2000) revealed a role for Gcn5 HAT complex components. These and other ingenious yeast assays will lend further insight into mechanisms underlying human MYST HAT function.…”
mentioning
confidence: 99%
“…It has been reported that retinoic acid receptor-dependent signaling is facilitated by SRC-3 (19). Following all trans-retinoic acid (ATRA) treatment, p38 MAPK is activated in metaplastic Barrett's cells (20), NB-4 human acute promyelocytic leukemia cell line, and MCF-7 human breast carcinoma cell line (21).…”
Section: Introductionmentioning
confidence: 99%